Happy Now? A Foucauldian Analysis of the World Happiness Report 2021 - Devey, Zak (New Zealand Sociology, 2023)
This article draws upon Foucauldian theory to consider the World Happiness Report 2021 (WHR 2021) as a site of psy-professional power. By detailing the distinct overlap between pathologising and seemingly strengths-based psy-discourses, I argue that institutions dealing in dominant happiness discourse can coerce subjects into understanding their emotionality in the likeness of happiness technologists and economic theorists. Using the WHR 2021 as a case study in the dissemination of such psy-professionalised happiness discourse, the article will then demonstrate how the text is capable of informing the socio-emotional dictates of other institutional discourses, including the New Zealand Government’s 2021 Wellbeing Budget as an example. The article concludes by calling for further interrogation of dominant happiness discourses using alternative theoretical frameworks, better illuminating the discursive influence of texts such as the WHR 2021 upon individuals and institutions alike.